RELEVANSI KONSEP PENDIDIKAN AKHLAK IBNU MISKAWAIH TERHADAP PENDIDIKAN KONTEMPORER - Mar'atus Solikhah; Dhuhrotul Khoiriyah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract. The concept of moral education with contemporary education cannot be separated from one another. Morals are very important in Islamic studies. As the Messenger of Allah was sent by Allah SWT, the first time was to perfect human morals. Morals are a reflection of the heart. As stated by Ibnu Miskawaih, morality is a psychological condition that encourages humans to do something with pleasure without any planning and thinking or deep consideration. Apart from that, Ibnu Miskawaih also talked about the universal education system that can be applied in the current era. The basis for the success of Islamic education lies in the causal relationship between the education system and moral improvement. The purpose of this study is to determine the relevance of Ibn Miskawaih's moral education to contemporary education. And this research uses a qualitative approach with the library research method. As for this study, there is relevance between the concept of Ibn Miskawaih's moral education and contemporary education applied in the 2013 curriculum Keywords: Education, Morals, Ibn Miskawaih.